Penghimpunan Dan Distribusi Zakat Penghasilan Serta Dampaknya Terhadap Kesejahteraan Ekonomi Keluarga Muslim Di Kota Binjai Pada Masa Pandemi Covid-19 - Adelia Zahra Harahap; Chuzaimah Batubara; Rahmi Syahriza (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The world is being rocked by a major pandemic called the Covid-19 Pandemic. The increasing number of patients infected with the Covid-19 virus is becoming increasingly difficult to control. Until this research was written, there were 4.58 million positive confirmed cases of Covid-19 in Indonesia. Not only the government, but social institutions also contributed to the existing problems. One of these social institutions is BAZNAS. The Indonesian Ulema Council issued fatwa number 23 of 2020 concerning the use of zakat, infaq, and alms funds for post-pandemic handling of Covid-19. Income zakat is one type of zakat that has a big role. Therefore, this study aims to find out how Binjai City BAZNAS collects and distributes zakat income funds and determines its impact on the economic welfare of Muslim families. Using qualitative research methods, we can find out that the role of income zakat funds is very large in helping Muslim families in Binjai City.